PENGEMBANGAN PARIWISATA PERKOTAAN BERBASIS KOMUNITAS : STUDI PADA KAMPUNG WISATA DIPOWINATAN YOGYAKARTA - Ida Susi Dewanti; Adi Soeprapto (Jurnal Ilmu Administrasi dan Bisnis, 2019)
Urban tourism is growing today along with a shift in the behavior of tourists and the tourism industry that is more oriented to tourism destinations and create new experiences. The city of Yogyakarta as the tourist city destination have great potency visited many tourists every day. One of successful tourist village at Yogyakarta city is Dipowinatan tourist kampong. Dipowinatan tourist kampong managed to build itself into a tourist destination place, not only domestic tourists as the main market even international tourists.This study use qualitative approach. Interviews as the main instrument for data collection. Respondents of this research were managers of village tourism as a key informant, some residents, and the government represented by the tourism department of Yogyakarta. The results showed that urban tourism through the development of the tourism kampong has an opportunity in the future. Traveler more interested with natural travel and experienced the daily life of a society. One of the facing obstacle  is public participation. The public will be fully support when they feel that the existence of tourist kampong can bring financial benefits and improve their welfare or they played an important role. So the presence of the public supports tourism kampong self-reliant and sustainable.  Keywords: urban tourism, tourism kampong, community participation.